The Effect of tau-fluvalinate on Amblyseius swirskii Athias-Henriot and Euseius scutalis Athias-Henriot (Acari: Phytoseiidae) - Serdar Satar; Adnan Tusun; Miraç Yayla; Gülsevim Tiring (Turkish Journal of Agriculture: Food Science and Technology)
Amblyseius swirskii Athias-Henriot (Acari:Phytoseiidae) and Euseius scutalis Athias-Henriot (Acari: Phytoseiidae) are important predatory mites for citrus orchards in Turkey. The side effects of insecticides on these predatory mites have been rarely studied. In this study was investigated to the effect of tau-fluvalinate on A. swirskii and E. scutalis. The studies have conducted both laboratory and field. Field studies were carried out detecting of the side effects of tau-fluvalinate on the mixed stages of A.swirskii. and E scutalis. at Seyhan and Kozan districts in Adana, while laboratory studies were evaluated the side effects of tau-fluvalinate on the nymph stages of A. swirskii The studies were carried out following the standard guidelines which were adopted and issued by the IOBC-WPRS Working group ‘Pesticedes and Benefical Organism’. In the field studies, the effects of the pesticides were calculated according to the Henderson-Tilton formula. As a result of study, tau-fluvalinate was determined as toxic on predatory mites in the laboratory studies. Side effects of abamectin, one of the standard toxic acaricides, on predatory mites were found to be “T” (Toxic) according to IOBC class value. Side effects of tau-fluvalinate were found to be ’M’’ (Moderately Harmful) on 7th days while were detected to be “N” (Harmless) on 28th days according to IOBC class value in field condition. The fields studies at Kozan and Seyhan districts showed similar results.